Energaia: Imagining Energy Futures - Robertson, Rachel; Bender, Stuart; Broderick, Mick; Castleden, Susanna; Messham-Muir, Kit; Chrulew, Matthew; Dooley, Kath; Ely, Philip; Frohlich, David; Johnston, Michelle; Goldrick, Sally; Kerr, Thor; et al. (John Curtin Gallery, 2022)
This publication supports the exhibition Energia: Imaging Energy Futures. John Curtin Gallery 28 March - 8 May 2022